1994
DOI: 10.1111/j.1600-0765.1994.tb01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of gingival and alveolar bone status in periodontitis‐affected hamsters treated with 15‐methyl prostaglandin E1

Abstract: Exogenous PGE1 at pharmacological doses suppresses acute and chronic inflammation manifestations. As periodontitis possesses features of both acute and chronic inflammation, attenuation of periodontal destruction in hamsters was attempted by using 15-M-PGE1, a stable PGE1 analog. The agent was tested at 2 different doses (100 and 150 micrograms/kg/d) and its effects were matched against disease-free and periodontitis-affected animals. No effect was found with the 100 micrograms regimen. In contrast, in the 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…it has becin shown that PG analogs ol' the F -scrics hax\c antiinflammatory activities suchI as prevention ol adjU\ Jt1 arthritis, inhibitioni of edema torimation, suppiessioln ol Iloinflammatory cytokine release (ZtII ier and QuaL' ,t 971; 1 959 .,s,, -,Y, ,YQ Perretti, 1994;Strassmann et al, 1994;Widomski et al, 1997). Furthermore, PG analogs of the Eseries have been demonstrated to induce periodontal regeneration in adult dogs and to inhibit gingival inflammation and bone resorption in periodontitis-affected hamsters (Capillon and Saffar, 1994;Marks and Miller, 1994). It has been suggested that ICAM-l expressed in HGF may play an important role in the accumulation and retention of LFA-1-bearing lymphocytes in periodontal lesions (Crawford et al, 1992;Hayashi et al, 1994;Takahashi et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…it has becin shown that PG analogs ol' the F -scrics hax\c antiinflammatory activities suchI as prevention ol adjU\ Jt1 arthritis, inhibitioni of edema torimation, suppiessioln ol Iloinflammatory cytokine release (ZtII ier and QuaL' ,t 971; 1 959 .,s,, -,Y, ,YQ Perretti, 1994;Strassmann et al, 1994;Widomski et al, 1997). Furthermore, PG analogs of the Eseries have been demonstrated to induce periodontal regeneration in adult dogs and to inhibit gingival inflammation and bone resorption in periodontitis-affected hamsters (Capillon and Saffar, 1994;Marks and Miller, 1994). It has been suggested that ICAM-l expressed in HGF may play an important role in the accumulation and retention of LFA-1-bearing lymphocytes in periodontal lesions (Crawford et al, 1992;Hayashi et al, 1994;Takahashi et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Local application of prostaglandin E 1 has been shown to stimulate bone formation adjacent to the site of delivery in the canine mandible (72). The use of a stable prostaglandin E 1 analog in a hamster periodontitis model improved bone status (11). It has also been reported that local delivery of prostaglandin E 1 increases cementum, alveolar bone, and periodontal ligament cell formation in adult dogs (73).…”
Section: Effect Of Prostaglandin E2 On Bone Metabolism and Periodontamentioning
confidence: 99%
“…Other evidence suggests that the same agents may also stimulate bone formation. The use of a stable PGE1-analog in a hamster periodontitis model controlled alveolar bone resorption (Caillon & Saffar 1994). Miller & Marks (1988, 1933a, b, 1994 have shown that local application of PGE1 in adult dogs stimulates alveolar bone formation in a dose-dependent manner, and formation of cementum and periodontal ligament.…”
mentioning
confidence: 99%